If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -4 = 8x + 7 Reorder the terms: -4 + 7x = 8x + 7 Reorder the terms: -4 + 7x = 7 + 8x Solving -4 + 7x = 7 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -4 + 7x + -8x = 7 + 8x + -8x Combine like terms: 7x + -8x = -1x -4 + -1x = 7 + 8x + -8x Combine like terms: 8x + -8x = 0 -4 + -1x = 7 + 0 -4 + -1x = 7 Add '4' to each side of the equation. -4 + 4 + -1x = 7 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 7 + 4 -1x = 7 + 4 Combine like terms: 7 + 4 = 11 -1x = 11 Divide each side by '-1'. x = -11 Simplifying x = -11
| -2x+5y=2 | | 3a-p=r | | n=0.03-59.08 | | 2(-1.3181818)-3y=4 | | x+5.5x=397 | | 5x+25=2x+73 | | 2(x+3)=2(x-3) | | 5+25=2+73 | | x-5.5x=397 | | (2x-9)=33 | | e*779942286= | | -5+3x=9 | | 3x^2+4x=15+y | | 3(x-4)+5=14 | | 4z+3(5-z)=-(z-1)+12 | | 5x-3x=10+3x-3x | | 4(z^2+z-2)=-2z^2-7z+2 | | 12345678*87654321=1 | | 14=-4x-6 | | 52-9x=2x+19 | | 4(z^2+11z-2)=-2z^2-7z+2 | | 9-45+8*4=778*x | | .33x+.67x=10 | | 100P=2400 | | 3=-6x-9 | | 3.5x-1.5x=18 | | .07x=1.4 | | 2w(-6-1)= | | 20x^2-27x=14 | | 2x+9=29-3x | | 58-7x=29x+18 | | t^2-t+1=0 |